Thirty Years' War - the uprising of the Silesian dukes and estates against the royal power in 1618: the right to active resistance or an act of rebelion? - Wąs, Gabriela (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych. Instytut Historyczny, 2018)
The aim of the article was an attempt to answer the question whether the uprising of the Silesian dukes and estates against the Habsburg kings in 1618–1621 had a rebellious character or whether it was an action taken under the right to active resistance guaranteed to them by the Bohemian kings. The subject of consideration were also the motives of armed actions of the Silesian dukes and estates during the Thirty Years’ War, both that at the beginning of the war and the second one from 1633–1635. Options were considered between the perception of conflict as a religious war (denominational motives) and the perception of it as a war conducted in the name of political reasons.
Keywords: Thirty Years' War; Silesia; Silesian estates; uprising; rebellion